Headless C1q: a new molecular tool to decipher its collagen‐like functions. (14th September 2020) - Fouët, Guillaume; Bally, Isabelle; Signor, Luca; Häußermann, Katharina; Thielens, Nicole M.; Rossi, Véronique; Gaboriaud, Christine
Abstract : Complement component C1q, a soluble defense collagen, is the recognition protein of the classical complement pathway. C1q is able to recognize and interact with multiple targets and, via the subsequent activation of its cognate serine proteases C1r and C1s, initiates the complement cascade. C1q is made up of six ABC heterotrimers each containing two different functional regions, an N‐terminal collagen‐like region (CLR) and a C‐terminal globular region (GR). These heterotrimers assemble via their N‐terminal regions, resulting in the characteristic 'bouquet‐like' shape of C1q with an N‐terminal bundle of collagen fibers with six diverging stems each exhibiting a C‐terminal globular head. The GRs are responsible for the versatile recognition of multiple C1q targets, whereas the CLRs trigger immune response through interacting with several cellular or soluble partners. We report here the generation of the first recombinant form of human C1q without its recognition globular heads. The noncollagenous domain 2 (nc2) of type IX collagen has been substituted for the C1q GR in order to control the correct registering of the collagen triple helices of C1q chains A, B, and C. The resulting CLR_nc2 recombinant protein produced in stably transfected EXPI293 mammalian cells was correctly assembled and folded, as demonstrated by mass spectrometry, mass photometry, and electron microscopy experiments. Its interaction properties were investigated using surface plasmon resonance analysis with known CLR ligands: the tetramer of C1r and C1s dimers and MBL‐associated protein MAp44. Comparison with the interaction properties of native serum‐derived C1q and CLR revealed that recombinant CLR_nc2 retains C1q CLR functional properties. Abstract : Replacement of C1q globular regions (GR) by type IX collagen nc2 domains allows the recombinant production of well‐assembled and folded C1q collagen‐like regions (CLR). This represents the first reported production of a chimeric C1q devoid of its GR functions while retaining CLR properties. Such development is of great interest and opens the way to molecular investigations of CLRs major functions such as complement activation and immune modulation.